2012
DOI: 10.1097/mpg.0b013e31824887a0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Early and High Amino Acid Supplementation on ELBW Infants at 2 Years

Abstract: ELBW infants who received early and high IV AA during the first week of life were associated with poor overall growth at 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
112
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(116 citation statements)
references
References 20 publications
4
112
0
Order By: Relevance
“…Eight studies compared low- versus high-dose amino-acid supplementation [13,16,23,24,25,26,27,28], 5 studies compared early versus late supplementation [12,29,30,31,32], and 3 studied both [16,33,34,35]. Three studies, from Blanco et al [33,34,35], were based on the same study population and were, therefore, seen as one. Six studies included co-interventions in their feeding protocol: 2 compared early versus late amino-acid supplementation [12,32] and 4 studied low- versus high-dose supplementation [13,25,27,28].…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies compared low- versus high-dose amino-acid supplementation [13,16,23,24,25,26,27,28], 5 studies compared early versus late supplementation [12,29,30,31,32], and 3 studied both [16,33,34,35]. Three studies, from Blanco et al [33,34,35], were based on the same study population and were, therefore, seen as one. Six studies included co-interventions in their feeding protocol: 2 compared early versus late amino-acid supplementation [12,32] and 4 studied low- versus high-dose supplementation [13,25,27,28].…”
Section: Resultsmentioning
confidence: 99%
“…Other investigators have reported similar results. [1][2][3][4][5] Establishing a consensus regarding what represents a normal metabolic profile in premature infants would allow investigators to identify infants with abnormal values and to evaluate the impact of those abnormal values on important health outcomes (liver injury, growth, and neurodevelopmental outcomes). Failure to establish normal values undermines our understanding of amino acid and fatty acid metabolism in premature infants.…”
mentioning
confidence: 99%
“…Choudri et al 69 found smaller brain growth and compromised neurodevelopment despite equivalent weight gain in preterm piglets receiving total parenteral in comparison with total enteral nutrition. Blanco et al 70 found that infants receiving an immediate parenteral amino acid intake of 2 g/kg/day increasing to 4 g/kg/day, compared with a group randomised to receive a lower intake, had a lower mean Mental Development Index at 18 months and lower mean z-scores for weight, length and head circumference. Reassuringly, in the NEON trial we identified no between-group differences in brain volume.…”
Section: Resultsmentioning
confidence: 99%